Accuracy of Structure from Motion models in comparison with terrestrial laser scanner for the analysis of DBH and height influence on error behaviour - D. Panagiotidis; P. Surový; K. Kuželka (Journal of Forest Science, 2016)
With the advantage of Structure from Motion technique, we reconstructed three-dimensional structures from two-dimensional image sequences in a circular plot with a radius of 6 m. The main objective of this research was to clarify the potential of using a low cost hand-held camera for evaluation of the stem accuracy reconstruction, through the comparison of data from two different point clouds. The first cloud comprises data collected with a digital camera that are compared with those collected by direct measurement of the FARO® Focus3D S120 laser scanner. Photos were taken in a circular plot of pine trees using the stop-and-go method. We estimated the Euclidean distance for corresponding points for both clouds and we found out that most of the points with error less than 11 cm are concentrated mainly on the ground. Regression analysis showed a significant relationship between height above ground and error, the error is more pronounced for points located higher on the stems. As expected, no dependence was found between the error of the points and the diameter at breast height of their respective stems.